2001
DOI: 10.1002/1097-0142(20010801)92:3<634::aid-cncr1364>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of glucose transporter-1 in human gastric carcinoma

Abstract: BACKGROUND Malignant cells show increased glucose uptake in vitro and in vivo, which is believed to be facilitated by glucose transporters (Gluts). Expression of Glut1, one of the Gluts, has been described in malignancies of the esophagus, colon, pancreas, lung, and brain, but to the authors' knowledge the significance of Glut1 expression in human gastric carcinoma has not been elucidated. The objective of the current study was to examine the expression and distribution of Glut1 and its relation to clinicopath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(87 citation statements)
references
References 31 publications
(34 reference statements)
6
80
1
Order By: Relevance
“…They reported that the detection rate of the diffuse type, according to Lauren's classification, (41%) was significantly lower than that of the intestinal type (83%), and they noted that this phenomenon may be due to the mucin content in diffuse-type gastric cancer, which has a diffuse growth pattern. Their data are supported by the findings of another study, showing low expression of glucose transporter-1 (Glut-1) in signet ring cells and mucinous gastric carcinoma [12]. In the present study, the detection rate of the intestinal type (65.5%) was higher than that of the diffuse type (51.5%) overall, but the difference was not significant.…”
Section: Sensitivity Of Detection Of Primary Gastric Cancer By Fdg-petsupporting
confidence: 88%
See 1 more Smart Citation
“…They reported that the detection rate of the diffuse type, according to Lauren's classification, (41%) was significantly lower than that of the intestinal type (83%), and they noted that this phenomenon may be due to the mucin content in diffuse-type gastric cancer, which has a diffuse growth pattern. Their data are supported by the findings of another study, showing low expression of glucose transporter-1 (Glut-1) in signet ring cells and mucinous gastric carcinoma [12]. In the present study, the detection rate of the intestinal type (65.5%) was higher than that of the diffuse type (51.5%) overall, but the difference was not significant.…”
Section: Sensitivity Of Detection Of Primary Gastric Cancer By Fdg-petsupporting
confidence: 88%
“…The uptake of FDG in malignant cells is reported to be correlated with the tumor growth rate [13] and with the number of viable cells [14]. Also, Kawamura et al [12] found that the expression of glucose transporter-1 (Glut-1) in gastric cancer was associated with parameters of aggressiveness of the tumor, such as depth of invasion, lymphatic permeation, venous invasion, nodal involvement, and hepatic metastasis. Therefore, a positive PET finding may demonstrate malignant aggressiveness, even in EGCs, and this may be an indicator of the extent of the lymphadenectomy required.…”
Section: Sensitivity Of Detection Of Primary Gastric Cancer By Fdg-petmentioning
confidence: 99%
“…Overexpression of the facilitative glucose-transporter has been observed for a wide range of human cancers (41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58) with the degree of overexpression generally being inversely correlated with prognosis. The mechanisms by which GLUTs promote malignant cellular behaviour have focused on factors inducing its expression, such as local hypoxia (37), oncogenes such as Ras, Scr (15) or Myc (38).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in gastric carcinomas the frequent occurrence of a diffuse growth pattern together with deposition of extracellular or intracellular mucus may lead to a reduced density of FDG-accumulating cells within the tumour. In addition, preliminary studies have indicated low expression of Glut 1 transporters in mucin-containing gastric carcinomas [16].…”
Section: Possible Reasons For the Low Detection Rate In Gastric Carcimentioning
confidence: 99%